Can MRI knee joint measurements predict the population at risk of ACL injury? - Mohammad Hamdan; Bassem Haddad; Mohammad Ali Alshrouf; Muayad I. Azzam; Ula Isleem; Reem Hamasha; Omar M. Albtoush; Muna Tayel Alhusban; Nidaa Mubarak; Saif Aldeen Alryalat (BMC, 2022)
Abstract Background Anterior cruciate ligament (ACL) injuries have been increasing significantly over time. The relationship between the ACL injury and the knee joint structures is poorly understood. The purpose of this study is to examine whether the measurements of different structures in the knee joint are linked with ACL injury in affected patients. Methods This retrospective case-control study included patients who suffered from ACL tears and underwent magnetic resonance imaging (MRI). A control group of patients with no knee pathologies on MRI was included. Fourteen knee variables, including lateral meniscus (LM) posterior horn height, length, depth, and volume; medial meniscus (MM) posterior horn height, length, depth, and volume; lateral and medial (MFC) femoral condyle sphere diameter; lateral and medial tibial plateau length; and patella tendon horizontal and vertical diameter, were collected. A multivariate logistic regression including LM posterior horn depth, MM posterior horn length, MM volume, MFC sphere diameter, and patella tendon horizontal diameter and receiver operating characteristic curve, was used to compare the two groups. Results A total of 85 patients were included in our study; 54 suffered from ACL injuries and 31 as a control group with normal knee MRI. Logistic regression revealed that increased LM posterior horn depth (OR = 1.27; 95% CI = 1.03-1.56; p = 0.028), decreased MM posterior horn length (OR = 0.71; 95% CI = 0.55-0.93; p = 0.013), and MFC sphere diameter (OR = 1.20; 95% CI = 1.01-1.43; p = 0.035) were independent risk factors for ACL rupture. The MFC sphere diameter yielded the highest area under the curve: 0.747 (95% CI, 0.632-0.862). No difference was found in the other measurements between the two groups. Conclusions Concerning the difference in anatomical variations, the lateral meniscus posterior horn depth and medial femoral condyle sphere diameter were higher, while medial meniscus posterior horn length was lower in patients with an ACL injury. These structural knee measurements could have a possible increase in the likelihood of sustaining an ACL injury and can be used by clinicians to predict ACL injury.